The Effect of Financial Compensation and Conflict on The Performance of Employees of The Loading and Unloading Warehouse at PT. Cahaya Indah Sangsurya in Pekanbaru - R. Rudi Alhempi; Irsyadi Zain; Jhonni Ardan Mardan; Faira Medina Dzikra (Lafadz Jaya Publisher, 2023)
The purpose of this study was to determine the effect of financial compensation and conflict on the performance of the loading and unloading warehouse employees at PT Cahaya Indah Sangsurya in Pekanbaru. The population in this study were all employees of the loading and unloading warehouse who worked at PT Cahaya Indah Sangsurya Pekanbaru totaling 42 (forty-two) respondents. In this study, because the population was small (limited), it was not possible to use a sample, so the researchers took the same number of samples as the population or called a census, namely all loading and unloading employees at PT Cahaya Indah Sangsurya Pekanbaru totaling 42 (four two) respondents. The power-gathering method used in this research is field research, which is carried out by conducting direct visits to the institutions that are the object of obtaining primary and secondary data. Based on the results obtained, it can be concluded that financial compensation and work conflict affect the performance of employees at PT Cahaya Indah Sangsurya Pekanbaru. The better the value of financial compensation and the lower the value of work conflict, the higher the value of employee performance.